Dramaturger om dramaturgi: enquete - Branth, Janicke; Bille, Karen-Maria; Holm, Bent; Hammershøy Nielsen, Benedikte; Lund Joensen, Hanne; Hassing, Louise W.; Wolf Iversen, Mette; Fentz, Christine; Langkilde, Nicole M.; Holm Thomsen, Trine (Peripeti, 2008)
Ten Danish dramatrugs from different theatrical fields tell about their daily work and experoences, and their visions for the changing role of the dramaturg in contemporary theatre